2016
DOI: 10.1001/jama.2016.17573
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Learning Environment Interventions and Medical Student Well-being

Abstract: Importance-There are concerns about the current quality of undergraduate medical education (UME) and its effect on students' well-being.Objective-This systematic review was designed to identify best practices for UME learning environment interventions that are associated with improved emotional well-being of students.Data Sources-Learning environment interventions were identified by searching the biomedical electronic databases Ovid MEDLINE, EMBASE, the Cochrane Library, and the ERIC database from the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
209
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(233 citation statements)
references
References 84 publications
5
209
0
11
Order By: Relevance
“…9,97,98 Modifiable stressors also need to be addressed to improve well-being. As a recent systematic review 99 revealed, there is no satisfactory evidence that learning environment interventions could contribute to improved mental well-being in medical students; additional high-quality research is needed in this area. We observed that signs of lack of motivation (e.g., thoughts of dropping out, dissatisfaction with the course, decreased academic efficacy) and lack of emotional support were associated with MHP, as in medical students from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…9,97,98 Modifiable stressors also need to be addressed to improve well-being. As a recent systematic review 99 revealed, there is no satisfactory evidence that learning environment interventions could contribute to improved mental well-being in medical students; additional high-quality research is needed in this area. We observed that signs of lack of motivation (e.g., thoughts of dropping out, dissatisfaction with the course, decreased academic efficacy) and lack of emotional support were associated with MHP, as in medical students from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous interventions to reduce burnout and promote wellbeing among healthcare workers have targeted the work environment and individual behaviors or cognitions (e.g., coping) (Panagioti et al, 2016; Ruotsalainen et al, 2015; Wasson et al, 2016). In general, the quality of evidence for such interventions is low, and depending on the exact population of healthcare workers and the type of organization being examined, institution-level interventions may be more or less effective (Panagioti et al, 2016; Ruotsalainen et al, 2015; Wasson et al, 2016). Our results could inform development or improvement of future interventions in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…The model is also thought to combine aspects of various other approaches to medical student mental health, including individual skill-building programs such as mindfulness, mentoring, and curriculum-based programs that target student health and wellbeing. In this way, the model is thought to answer the call for more comprehensive reform of the medical education environment (Wasson et al, 2016) and incorporation of multiple strategies to target student mental health. However, it must be noted that there is a long way to go in furthering the implementation of the model and consequent revisions over time.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of these various wellbeing-based interventions within the medical student population concluded that some specific learning environment interventions were found to be associated with improved wellbeing amongst students (Wasson et al, 2016). More specifically, the review recommended 'comprehensive reform' within the learning environment, that incorporates a range of targeted interventions, as most likely to be effective.…”
Section: The Medical Student Journeymentioning
confidence: 99%